2008
DOI: 10.1038/sj.bjc.6604436
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analyses of chemotherapy for locally advanced and metastatic pancreatic cancer: results of secondary end points analyses

Abstract: In advanced pancreatic cancer, level one evidence has established a significant survival advantage with chemotherapy, compared to best supportive care. The treatment-associated toxicity needs to be evaluated. This study examines the secondary outcome measures for chemotherapy in advanced pancreatic cancer using meta-analyses. A systematic review was undertaken employing Cochrane methodology, with search of databases, conference proceedings and trial registers. The secondary end points were progression-free sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 42 publications
3
54
1
4
Order By: Relevance
“…37 The reviews showed that chemoradiation followed by chemotherapy did not demonstrate any survival advantage over chemotherapy alone. There was a significant survival benefit for chemotherapy over best supportive care and gemcitabine combinations over gemcitabine alone including gemcitabine with capecitabine.…”
Section: Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…37 The reviews showed that chemoradiation followed by chemotherapy did not demonstrate any survival advantage over chemotherapy alone. There was a significant survival benefit for chemotherapy over best supportive care and gemcitabine combinations over gemcitabine alone including gemcitabine with capecitabine.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…The combination of gemcitabine with capecitabine was chosen as this could potentiate the vaccine effects and was also associated with significantly improved objective responses compared to gemcitabine alone. 22,37,38 Interpretation This is one of the largest randomized clinical trials ever undertaken in pancreatic cancer and the largest trial of vaccine therapy ever undertaken in any solid cancer type. There was no survival benefit from the addition of the GV1001 vaccine to gemcitabine and capecitabine in patients with advanced pancreatic cancer.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…5-FU and gemcitabine are chemotherapeutic drugs commonly used for the treatment of pancreatic cancer (28). The ability of klotho to enhance their activity on pancreatic cancer cells was examined.…”
Section: Klotho Inhibits Growth Of Pancreatic Cancer Cells In Vitro Amentioning
confidence: 99%
“…Istnieje przynajmniej 8 metaanaliz dotyczących terapii łączonej z zastosowaniem gemcytabiny [68][69][70][71][72][73][74][75]. Wszystkie razem potwierdzają fakt, że gemcytabina jest nadal złotym standardem w terapii zaawansowanego raka trzustki, a terapia skojarzona przynosi pewne korzyści, lecz w porównaniu z monoterapią zwiększa odsetek działań niepożądanych oraz koszty.…”
Section: Terapia łąCzona Z Zastosowaniem Gemcytabiny W Zaawansowanym unclassified